(untitled) (Homoeopathy for All, 2021)
Sinuses are four pairs of air-filled cavities located in the skull in the region around the nose and the eyes. These sinuses are: • Frontal sinuses; located above the eyes, in the center region of each eyebrow • Maxillary sinuses; located within the cheekbones, just to either side of the nose • Ethmoid sinuses ; located between the eyes, just behind the bridge of the nose. • Sphenoid sinuses ; located just behind the ethmoid sinuses, and behind the eyes